La faculté articulatoire de l'apprenant irakien Dans une classe de français langue étrangère A l’université de Bagdad Etude comparative - AL-OBAIDI, Jinan mohammed watheq Ismael (Al-Adab Journal, 2019)
This research speaks of the ability of Iraqi student in pronunciation. First we describe the alphabet of Arabic and French language, while showing the specificity of some Arabic sounds. The one that characterizes our learner and facilitates his learning of the French language by an easy pronunciation of French sounds